Activated Pancreatic Stellate Cells Enhance the Warburg Effect to Cause the Malignant Development in Chronic Pancreatitis - Tao, Ye; Shao, Feng; Cai, Ming; Liu, Zhen; Peng, Yao; Huang, Qiang; Meng, Futao (Frontiers in Oncology, 2021)
Chronic pancreatitis (CP) is a precancerous condition associated with pancreatic ductal adenocarcinoma (PDAC), but its evolutionary mechanism is unclear. Pancreatic stellate cells (PSCs) are closely related to the occurrence and development of CP and PDAC, but it is not clear whether PSCs play a key role in this "inflammation-cancer transition". Our research found that co-culture with activated PSCs promoted the proliferation, migration and invasion of normal pancreatic duct epithelial cells and pancreatic cancer cells. At the same time, activated PSCs had a significant effect on the expression of the glycolytic enzymes pyruvate kinase M2 (PKM2) and lactate dehydrogenase A (LDHA) in normal pancreatic duct epithelial cells and pancreatic cancer cells and increased lactic acid production and glucose consumption in these two cells. In vivo experiments showed that the expression of the glycolytic enzymes PKM2 and LDHA in pancreatic duct epithelial cells and the marker protein (α-SMA) of activated PSCs in the pancreatic duct peripancreatic interstitium were higher in pancreatic cancer tissues and chronic pancreatitis tissues than in normal pancreatic tissues in both animals and humans. In addition, analysis of human tissue specimens showed that there is a correlation between the expression of PKM2/LDHA and α-SMA. These findings indicate that activated PSCs play an important role in the development and progression of chronic pancreatitis into pancreatic cancer by regulating and promoting aerobic glycolysis. Our research provides a new theoretical basis for further understanding the mechanism of CP malignancy and the selection of targets for reversing CP malignancy.